Repeat peritonitis in peritoneal dialysis : A cohort study - Nabil Hmaidouch; Sara El Maakoul; Hajar Fitah; Naima Ouzeddoun; Loubna Benamar (Bulletin de la Dialyse à Domicile, 2024)
Introduction: The understanding of the pathophysiological mechanisms of repeat peritonitis, defined as the occurrence of peritonitis more than 4 weeks after the end of appropriate antibiotic treatment for a previous episode involving the same germ, remains limited.